Theoretical model of Thunderstorm Winds near the ground - ASNANI, G. C. (MAUSAM, 1961)
Based on some assumptions about the horizontal and vertical variation of a downdraft emanating from the base of a thundercloud, a quantitative estimate of the position and the magnitude of squall near the ground is presented. It appears that squall occurs nearer to the periphery of the downdraft than to its central axis. Also downdraft velocities of the order of 5 meters per second in the lowest 500 meters above the ground are quite capable of generating squall speeds near the ground of as much as 50 meters per second. Also, squall speed is greatly influenced by the horizontal extent of the downdraft; the larger the horizontal extent of the downdraft; the larger the horizontal extent of the downdraft, the larger the squall speed.